Satisfaction of Livable House Assistance Recipients with the Implementation of the Self-Help Housing Stimulant Assistance Program - Atmaja, Wahana Riyan; Devi, Sihtasari; Hermawan, Ferry; Sriyana, Sriyana (International Journal of Social Service and Research, 2023)
The house is one of the primary needs that must be met by Indonesian people who do not meet livable standards. One of the efforts to be carried out in the infrastructure section, aims so that people get a decent place to live. To realize having a livable house must be planned and prepared properly. This research is reviewed from the problem of many houses that do not yet have decent housing standards. The Government's Self-Help Housing Stimulant Assistance (BSPS) is intended to encourage and increase the self-sufficiency of low-income people in improving the quality of their homes, as seen from the quality of roofs, floors and walls of the house along with infrastructure, public facilities and facilities that meet health, safety, comfort requirements. and bathroom facilities. In the BSPS program as an alternative to poverty alleviation policies by providing direct material assistance for the housing construction process. Based on the intent of the BSPS program objectives according to the BSPS program implementation team in Indonesia, especially in Rembang Regency, the aim of the BSPS program is to improve the quality of life of low-income people to obtain livable housing. that most people respond well to the BSPS program in Japrejo Village and Sumberejo Village Recipients of the Self-Help Housing Stimulant Assistance Program (BSPS), however, it is not uncommon for people to refuse due to limited funds which are considered insufficient. Satisfaction of building recipients after receiving assistance from Self-Help Housing Stimulant Assistance (BSPS) in obtaining assistance. Construction/improvement of houses for low-income people to ensure their quality meets the livable requirements of the BSPS program where assessment is carried out in the Structural and Non-Structural sections according to the house criteria livable